A COST-EFFECTIVE IOT-BASED FOOTFALL COUNTING SYSTEM USING PIR SENSORS - Butani, Ravi C.; Bhavsar, Jignesh K.; Bhatt, Nisarg K. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Footfall refers to the number of people present in, or who have passed through, a given location during a specific period. Accurate footfall data is a vital metric that, when analyzed, can yield valuable insights such as conversion rates, traffic heatmaps, planning strategies, and occupancy indices. Traditional counting methods employ manpower or automated systems such as turnstiles, camera-based detection, radio-frequency fingerprinting, and various transducers (ultrasonic, force, infrared). However, these approaches present challenges including high deployment cost, maintenance requirements, privacy concerns, and inconsistent accuracy. This project proposes a cost-effective IoT-based solution utilizing Passive Infrared (PIR) sensors for footfall counting. The system is designed to deliver comparable functionality to existing commercial solutions while eliminating privacy risks and significantly reducing cost and maintenance overhead. The integration of IoT capabilities further enables real-time monitoring and data analysis, making the solution well-suited for applications in smart infrastructure, retail, and institutional environments.